Whole-cell biosensors: research and patents - Fernandez, Marcelo Raul (2010)
In the last ten years several research articles and patents related to the obtaining and uses of whole-cell biosen- sors (WCB) have been published. Whole-cell sensors, whole-cell biosensors, chemical sensors, integrated sensors and bioreporters (among others) are the main terms used to define a living cell machinery adapted to detect target analytes at low concentration levels. The methods for constructing and detection technologies for these WCB could be very diverse. Some of them include a foreign nucleic acid sequence to act as reporter, to regulate the reporter’s expression or both. But some other inventors ex- ploit the natural properties of organisms without the need of genetic engineering. Another aspect is the localization of the cell at the moment of use. Some inventors, depending on the method of detection, need cells in a special location, such as the surface of a detector, entrapped in a matrix, or in the bulk of the sample. This review intends to compile the most rele- vant patents related to WCB which enable to illustrate the above mentioned cases of these new types of biosensors.